The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00423-021-02142-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery during the COVID-19 pandemic: detection of SARS-COV-2 in abdominal tissues, fluids, and surgical smoke

Abstract: Background There are still concerns over the safety of laparoscopic surgery in coronavirus disease 2019 (COVID-19) patients due to the potential risk of viral transmission through surgical smoke/laparoscopic pneumoperitoneum. Methods We performed a systematic review of currently available literature to determine the presence of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) in abdominal tissues or fluids and in surgical smoke. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 44 publications
0
37
0
1
Order By: Relevance
“…But there has been a constant debate among the surgeons primarily due to the lack of a definitive evidence regarding the spread of the virus. 17 18 …”
Section: Discussionmentioning
confidence: 99%
“…But there has been a constant debate among the surgeons primarily due to the lack of a definitive evidence regarding the spread of the virus. 17 18 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, many surgical societies recommended restricted use of laparoscopy and diathermy during the pandemic [16]. However, with accumulation of experience and clinical data analysis, it was found that there was no significant perioperative SARS-CoV-2 infection transmission among the patients and healthcare workers with laparoscopy [15,17,18]. Hence, the new recommendation was to perform laparoscopic surgeries using appropriate precautions such as personal protective equipments, smoke evacuation devices, if it was clearly beneficial to the patients and reduced their hospital stay [19,20].…”
Section: Impact Of Covid-19 Pandemic On Gastrointestinal Surgical Servicesmentioning
confidence: 99%
“…Surgical smoke is considered to be one of the means of perioperative viral transmission based on the previous reports [21]. The SARS-CoV-2 virus has been found in the peritoneal fluid, bile, ascitic fluid and surgically resected specimens suggesting that the viruses are present in the operative field during the surgery [18,68]. But, the evidence to support that SARS-CoV-2 infection is transmitted by surgical smoke is lacking [15,17,18].…”
Section: Strategies To Reduce Perioperative Transmission Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Im Verlauf der Pandemie hat sich zwar die Evidenzlage etwas gebessert, was jedoch aufgrund gegensätzlicher Ergebnisse zu keiner vermehrten Sicherheit geführt hat [ 3 ]. Es bleibt somit ein potenzielles Risiko der intraoperativen SARS-CoV-2-Transmission im Rahmen kolorektaler Eingriffe bestehen und somit sind die eingangs erwähnten Sicherheitsmaßnahmen weiterhin zu empfehlen.…”
Section: Präoperative Risikoevaluation In Bezug Auf Covid 19unclassified